TRANSFORMASI REPRESENTASI SEJARAH DALAM SASTRA KONTEMPORER INDONESIA - Ratu Pangestu (PT. Habe Cendekia Utama, 2025)
The relationship between history and literature in Indonesia is strong and complementary, with history serving as a crucial source of inspiration for literary works. Indonesian historians and writers have demonstrated the close relationship between history and literature in Indonesian culture, where literary works often take the form of